2011
DOI: 10.1007/s12272-011-1210-0
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of glimepiride and its metabolites in human plasma by liquid chromatography coupled to a tandem mass spectrometry

Abstract: Glimepiride, a second-generation sulfonylurea, is a glucose-lowering agent widely used to treat diabetes mellitus. It is converted into metabolite M1 by CYP2C9, and M1 is then transformed into the carboxyl derivative M2 by cytosolic enzymes. In this study, we introduce a sensitive liquid chromatography/tandem mass spectrometry (LC/MS/MS) method for determining glimepiride, M1, and M2 in human plasma. After simple protein precipitation with acetonitrile, the analytes were chromatographed on a reversed-phase CN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…[12] Subsequently, several research groups developed the liquid chromatography-tandem mass spectrometry (LC-MS/MS) method for quantitative determination of glimepiride in human plasma. [13,14] Recently, the effect of SUs on biochemical changes in patients with T2DM was investigated through the metabolomic approach. [15] However, the effects of glimepiride on endogenous metabolomic alterations in healthy subjects remain poorly understood.…”
Section: Transl Clin Pharmacolmentioning
confidence: 99%
“…[12] Subsequently, several research groups developed the liquid chromatography-tandem mass spectrometry (LC-MS/MS) method for quantitative determination of glimepiride in human plasma. [13,14] Recently, the effect of SUs on biochemical changes in patients with T2DM was investigated through the metabolomic approach. [15] However, the effects of glimepiride on endogenous metabolomic alterations in healthy subjects remain poorly understood.…”
Section: Transl Clin Pharmacolmentioning
confidence: 99%
“…Glimepiride, a third‐generation sulfonylurea hypoglycemic agent, has been used for the treatment of type 2 noninsulin‐dependent diabetes mellitus 16,17 . The glimepiride metabolite appears to be formed by CYP2C9 in liver microsomes 18 . Although the efficacy of ginsenoside Rg3 and glimepiride in T2DM was confirmed by these studies, the mechanism of the effect of drug–drug interaction between ginsenoside Rg3 and glimepiride on cytochrome P450 enzymes is still not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Sitagliptin, one of the major DPP4 inhibitors, is eliminated primarily by renal excretion and only 16% of dose excreted as metabolites [5]. On the other hand, glimepiride, a second-generation sulfonylurea, is converted into M1 by CYP2C9 and carboxyl derivatives M2 by cytosolic enzymes [6]. Although several studies have demonstrated the safety of DPP4 inhibitors, studies directly comparing the effects and safety of SU upward titration treatment and combination treatment with low-dose SU and DPP4 inhibitors in Japanese diabetes patients have not been performed.…”
Section: Introductionmentioning
confidence: 99%